SOCIAL, POLITICAL AND CULTURAL ACTIVITIES OF BELARUSIAN IMMIGRATION IN 1918–1939 - M. V. Strelez; O. I. Bilevich (Гуманитарные и юридические исследования)
The article deals with some aspects of Belarusian emigration in the interwar period. The authors cover various activities of cultural organizations of Belarusian emigration.